A Comprehensive Research Review on Timber Post-Tensioning Technology - Yeap, Kuang Shen; Yeoh, David Eng Chuan (Recent Trends in Civil Engineering and Built Environment, 2021)
Wood also known as timber in the engineering term that is beneficial to all over the world by its contribution as an important construction material. Timber alike to other materials such as steel and concrete, which able to lead to rapid development of construction field in this era of globalization.  However, usage of timber is slightly less than steel and concrete in construction field including office and commercial building construction due to the long span length timber beam is easily deflect at the mid-span. From reliable reviews, prestressing of timber element also known timber post-tensioning technology introduced as an advance technology to enhance the tensile strength, bending stiffness and load bearing capacity of the timber in order to reduce the deflection at the mid span of long span timber beam and reduced the thickness of the timber beam as well. This study was conducted to determine the concept of the timber post-tensioning and its development history from past to present. Besides, the design of post-tensioning timber also a great concern, which can design as timber beams or frames under gravity and seismic loading consequently influenced its structural performance. From previous study, it illustrates that the strength and structural performance also influenced by post-tensioning losses in term of long-term behavior. Besides, several advantages are significantly by comparing the timber element with and without post-tensioning technology such as reduce deflection at the mid span, ecofriendly, time and cost saving.